Analisis Akuntabilitas Dan Transparansi Dalam Pengelolaan Zakat Infaq Dan Dana Sedekah Dompet Dhuafa Waspada Medan - Zahara, Annisa; Nurwani, Nurwani (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
This study aims to determine accountability and transparency in the management of Zakat and Alms Infaq funds at the Amil Zakat Institution, Dompet Dhuafa Waspada Medan. This type of research is qualitative, with a descriptive approach, data sources obtained through interviews, documentation, literature studies, and observation. This type of data analysis uses descriptive analysis, starting with data reduction, data presentation, then draws conclusions. The results of the study show that accountability for the management of ZIS Funds in Dompet Dhuafa is very good with a planned collection system and continued with programmed programs. The collected ZIS funds are channeled and utilized in the fields of education, religion, social justice and humanity, as well as economic empowerment with fair and equitable distribution. Whereas in terms of Transparency, Dompet Dhuafa Alert has been maximized and has met transparency indicators. Because Dompet Dhuafa has reported a consolidated report, a report on program beneficiaries that has been distributedDompet Dhuafa is transparent in terms of easy access, DDW provides easy access for the community, DDW has published every activity carried out, the number of beneficiaries every month, even every year on the official website and also Dompet Dhuafa Waspada social media. And in terms of publishing financial reports, Dompet Dhuafa Waspada Medan does not publish its financial reports on websites or social media, because the financial reports that have been managed by each Dompet Dhuafa branch office have been consolidated into the central Dompet Dhuafa, and have been published on the central web, even for the last year's financial report, namely 2022, the audit results have come out with an unqualified opinion, therefore it can be said that Dompet Dhuafa Waspada Medan Branch has been transparent in managing Zakat, Infak and Alms funds.